Epidemiologia quantitativa do oídio do cajueiro no clone BRS 189 - Lima, Joilson Silva (2017)
The cashew (Anacardium occidentale) is one of the main fruit trees cultivated and adapted to semi-arid tropical regions of the world. However, despite its rusticity, cashew plant is affected by a large number of diseases, mainly causaded by fungi. Among these, powdery mildew, caused by Pseudoidium anacardii is currently the main disease of this crop, affecting leaves, inflorescences, and fruits of the plant. Due to powdery mildew importance, the lack of detailed published studies which associate the effect of P. anacardii on the yield of A. occidentale and the absence of a standardized method to quantify severity in this pathosystem, the present study was developed to determin the relationship between the intensity of the powdery mildew and the cashew yield clone BRS 189, as well as to elaborate and validate a diagrammatic descriptive scale to evaluate powdery mildew severity. In order to evaluate the effect of powdery mildew on the clone BRS 189, an experiment was carried out in Pacajus, Ceará State, with eight treatments (T1 - 0 g, T2 - 0,5 g, T3 - 1 g, T4 - 2 g, T5 - 3 g , T6-4 g, T7-5 and T8-7 g enxofre/L water). The severity and incidence of powdery mildew was evaluated and data were correlated to the yield and biometric characteristics of fruits and pseudofruit (apples). On the other hand, the descriptive diagrammatic scale with levels 0 (Note 0), 5 (Note 1), 17.5 (Note 2), 37.5 (Note 3), 62.5 (Note 4) and 87.5% (5) was proposed, elaborated and tested for the accuracy, precision, and reproducibility of severity estimates of the disease on cashew fruits. The scale was validated by twenty persons (ten with experience and ten without experience) who used fifty nuts with different levels of severity. The results showed that the powdery mildew does not affect the nut yield in the cashew clone BRS 189, but causes a reduction in the weight and nut size, also compromising the weight, the size, and the quality of apples. In addition, the proposed scale proved to be easily used and improved the accuracy, precision and reproducibility, showing to be an excellent tool in epidemiological studies of the disease, field survey, resistance studies and control of the powdery mildew.